2008
DOI: 10.1590/s0074-02762008000800009
|View full text |Cite
|
Sign up to set email alerts
|

Resurrection of Anopheles goeldii from synonymy with Anopheles nuneztovari (Diptera, Culicidae) and a new record for Anopheles dunhami in the Brazilian Amazon

Abstract: Nucleotide sequences of the internal transcribed spacer 2 (ITS2) rDNA and partial sequences of the cytochrome coxidase subunit I (COI) mtDNA and white gene nDNA were obtained from specimens of Anopheles nuneztovari A collected in Macapá (state of Amapá), Óbidos, Prainha and Almeirim (state of Pará), Itacoatiara and Parintins (state of Amazonas), Brazil, and compared with previously published sequences of A. nuneztovari s.l. Results of the Bayesian phylogenetic analyses performed using either COI or combined IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
2
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 23 publications
2
53
2
7
Order By: Relevance
“…goeldii haplotypes found by Calado and others. 18 If these haplotypes represent An. goeldii , it also could exist in the eastern region of Amazonian Brazil, and its populations should be differentiated genetically.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…goeldii haplotypes found by Calado and others. 18 If these haplotypes represent An. goeldii , it also could exist in the eastern region of Amazonian Brazil, and its populations should be differentiated genetically.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28] Morphologic comparisons showed that the apex of the aedeagus is distinct between samples from the Amazon Basin and Colombia plus Venezuela. 3,18 These data combined with molecular analyses led to the resurrection of An. goeldii .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations